RANCANG BANGUN FUEL PUMP PRESSURE TESTER PADA MOTOR INJEKSI - Nasrullah, Hamid; Saputra, Ragil (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2019)
Pressurized fuel is fuel that is pumped by a fuel pump (fuel pump) from the fuel tank to the injector. Fuel pressure that is too low will greatly affect the performance of the engine and the risk of engine failure. Fuel pressure measurement aims to determine the performance of the fuel pump (fuel pump) is still able to work well or not. The method used is a qualitative method. The construction design starts from the planning process which includes making the concept of design, observation and processing of data so that it is found that the design is capable of reading fuel pressure from the fuel pump and is easy to use. To strengthen the results of the study, it is complemented by a literature review that has close relevance to the subject matter. Based on the results of testing that has been achieved from the entire process of making and testing the design of fuel pump pressure tester on injection motors, it can be concluded that the functional test in the last process shows that the tool can work well and is able to provide information on fuel pressure measurements from the fuel pump.